Russia and Countering Violent Extremism in the Internet and Social Media: Exploring Prospects for U.S.-Russia Cooperation Beyond the "Reset" - Sharyl N. Cross Dr. (Journal of Strategic Security, 2013)
Russia has been targeted with a series of terrorist attacks over the past several years, and there are a growing number of extremist groups operating throughout Russia’s society utilizing the Internet/social media to promote their narratives and objectives. Russia’s policy community has created institutional mechanisms and laws to address the challenge of violent extremism in the Internet/social media, and recognizes the importance of international cooperation toward these ends. This study, based on primary research conducted in Moscow in 2012, defines Russia’s assessment of domestic and international sources violent extremist threats; explains Moscow’s perspective on balancing democratic principles with the challenge of countering violent extremism in the Internet/social media; assesses existing capacities and impediments to further international collaboration with Russia in countering violent extremism in the Internet/social media spheres; defines specific initiatives that Russia, the United States, and other nations of the world community could advance to enhance international cooperation in countering violent extremism throughout the world cyber community.